Implementation of the competence approach with the help of network project activities - Lyudmila N. Bakhtiyarova, Alexander V. Ponachugin, Elvira K. Samerkhanova, Elena P. Krupoderova, Klimentina R. Krupoderova,; Kanyanina, Tatiana I. (Opción)
The article discusses the possibilities of implementing the competence-based approach to learning through project activities via use of methods of generalization, comparison and forecasting. As a result, the formation of important general professional competencies of future bachelors of pedagogical education occurs when students themselves are the developers of educational and network projects. An analysis of the capabilities of digital tools based on network services led to the conclusion that the project activity can create new unique network content and active interaction between its subjects, be the network applied practically.